Advanced biomedical image analysis - Haidekker, Mark A. 1963- (Hoboken, N.J. John Wiley & Sons, 2010)
"This book covers the four major areas of image processing: Image enhancement and restoration, image segmentation, image quantification and classification, and image visualization. Image registration, storage, and compression are also covered. The text focuses on recently developed image processing and analysis operators and covers topical research"--Provided by publisher.
Frontmatter -- Color Plates -- Image Analysis: A Perspective -- Survey of Fundamental Image Processing Operators -- Image Processing in the Frequency Domain -- The Wavelet Transform and Wavelet-Based Filtering -- Adaptive Filtering -- Deformable Models and Active Contours -- The Hough Transform -- Texture Analysis -- Shape Analysis -- Fractal Approaches to Image Analysis -- Image Registration -- Image Storage, Transport, and Compression -- Image Visualization -- Image Analysis and Visualization Software -- Appendix A: Image Analysis with Crystal Image -- Appendix B: Software on DVD -- Index -- Customer Note: If this Book is Accompanied by Software, please read the following Before Opening the Package --
Keywords: Diagnostic imaging -- Digital techniques; Image processing -- Digital techniques; Electronic books